2006
DOI: 10.1136/bmj.38985.646481.55
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of risk of death and myocardial infarction in the six months after presentation with acute coronary syndrome: prospective multinational observational study (GRACE)

Abstract: Objective To develop a clinical risk prediction tool for estimating the cumulative six month risk of death and death or myocardial infarction to facilitate triage and management of patients with acute coronary syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
969
5
77

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,347 publications
(1,078 citation statements)
references
References 29 publications
27
969
5
77
Order By: Relevance
“…In fact, a recent report from the GRACE (Global Registry of Acute Coronary Events) demonstrated that ≈5% of patients with ACS admission had died during the indexed hospitalization, and an additional 10% of patients experienced subsequent events, including death and MI within 6 months after discharge 19. In accordance with this previous report, the overall ACS admission was associated with an increased risk of long‐term mortality in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, a recent report from the GRACE (Global Registry of Acute Coronary Events) demonstrated that ≈5% of patients with ACS admission had died during the indexed hospitalization, and an additional 10% of patients experienced subsequent events, including death and MI within 6 months after discharge 19. In accordance with this previous report, the overall ACS admission was associated with an increased risk of long‐term mortality in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, we evaluated whether FI is a predictor of 6‐month all‐cause and cardiac‐specific mortality. Multivariable logistic regression models were used to estimate the marginal effect of FI separately by MI type (NSTEMI and STEMI) after adjusting for sex and GRACE (Global Registry of Acute Coronary Events) risk score 13, 14. Odds ratios (ORs) with 95% confidence intervals (CIs) were reported per 0.1 FI.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded patients with: ST‐segment elevation of ≥1 mm in 2 contiguous leads on the presenting ECG; any significant rise in cardiac troponin (>9th percentile); pretest probability <15%; Global Registry of Acute Coronary Events (GRACE) score >1408 known CAD or awaiting revascularization; history and clinical examination suggesting non‐cardiac chest pain; abnormal resting echocardiography and/or chest X‐ray; hemoglobin <13 g/dL; or thyroid disorder. No sex‐based or race/ethnicity‐based differences were addressed.…”
Section: Methodsmentioning
confidence: 99%